Revision and cladistic analysis of Neotropical genus Psilochlorops Duda (Diptera: Chloropidae) - Riccardi, Paula Raile; de Souza Amorim, Dalton (Zootaxa, 2012)
Five new species are described herein for the Neotropical genus Psilochlorops, up to now known only from the type–spe-cies, P. clavitibia Duda—P. brunneus sp. n., P. elongatum sp. n., P. flavisoma sp. n., P. nigrifemur sp. n. and P. paganelliaesp. n. All new species are described in detail and illustrated. A key to the species of the genus is provided. The diagnosisof Psilochlorops, after the addition of these species, is emended. A cladistic analysis of the genus indicates that Psilochlorops is monophyletic and show the affinities between the species.